Biomechanical comparison of straight and helical compression plates for fixation of transverse and oblique bone fractures: Modeling and experiments - Sezek, Sinan; Aksakal, Bunyamin; Gurger, Murat; Malkoc, Melih; Say, Y. (Ios Press, 2016)
T otal deformation and stability of straight and helical compression plates were studied by means of the finite element method (FEM) and in vitro biomechanical experiments. Fixations of transverse (TF) and oblique (45 degrees) bone (OF) fractures have been analyzed on sheep tibias by designing the straight compression (SP) and Helical Compression Plate (HP) models. The effects of axial compression, bending and torsion loads on both plating systems were analyzed in terms of total displacements. Numerical models and experimental models suggested that under compression loadings, bone fracture gap closures for both fracture types were found to be in the favor of helical plate designs. The helical plate (HP) fixations provided maximum torsional resistance compared to the (SP) fixations. The fracture gap closure and stability of helical plate fixation for transverse fractures was determined to be higher than that found for the oblique fractures. The comparison of average compression stress, bending and torsion moments showed that the FEM and experimental results are in good agreement and such designs are likely to have a positive impact in future bone fracture fixation designs.
Keywords: Straight and helical plates; transverse and oblique bone fractures; fixation